2015
DOI: 10.3390/jmse3041260
|View full text |Cite
|
Sign up to set email alerts
|

Longer-Term Mental and Behavioral Health Effects of the Deepwater Horizon Gulf Oil Spill

Abstract: Abstract:Mental health issues are a significant concern after technological disasters such as the 2010 Gulf Oil Spill; however, there is limited knowledge about the long-term effects of oil spills. The study was part of a larger research effort to improve understanding of the mental and behavioral health effects of the Deepwater Horizon Gulf Oil Spill. Data were collected immediately following the spill and the same individuals were resampled again after the second anniversary (n = 314). The results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…Using the same measure of depression we did, they found that depression scores between the 2 time periods remained largely unchanged. 38 Our results show an increase in depressive symptoms after a longer time interval and thus begin to provide some definitive evidence to support long-term health impacts of oil spills. 39 A possible explanation for the increase in depressive scores in the present study centers around the already heightened vulnerability of the study population due to previous disasters.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Using the same measure of depression we did, they found that depression scores between the 2 time periods remained largely unchanged. 38 Our results show an increase in depressive symptoms after a longer time interval and thus begin to provide some definitive evidence to support long-term health impacts of oil spills. 39 A possible explanation for the increase in depressive scores in the present study centers around the already heightened vulnerability of the study population due to previous disasters.…”
Section: Discussionsupporting
confidence: 63%
“…Our study reinforces other analyses of the DHOS of shorter duration. 30,31,38 For example, Hansel et al assessed recovery in 314 Gulf Coast residents in the first year following the DHOS (2010-2011) and again just after the second anniversary (2012). Using the same measure of depression we did, they found that depression scores between the 2 time periods remained largely unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…With few exceptions, 20,21 there have not been many studies to examine the longer term impacts of oil spills, measured years after the event, though many have stressed the importance of doing so. 3,20 Research on long-term impacts of other disasters and mass trauma events (eg, the DHOS, 21 September 11 attacks, 22 and Hurricane Sandy 23 ) suggests that most exposed individuals recover from immediate mental health effects. However, for some, these mental health problems may become chronic, whereas others may develop late-onset symptoms.…”
mentioning
confidence: 99%
“…Prevailing westerly winds during the following days spread the floating oil along the coast and reached the Côtes d'Armor one week after the accident. The 2010 Deepwater Horizon oil spill released around 780 million liters of crude oil into the water, and a considerable amount of this spilled oil first arrived on Alabama's shoreline ten days after the accident [7].…”
Section: Introductionmentioning
confidence: 99%